ANALISIS KEBERLANJUTAN HOME BASED ENTERPRISE PENGOLAHAN SINGKONG DI KOTA SALATIGA - Dwi Laras Lukitaningrum; Wido Prananing Tyas; Mohammad Muktiali (Diponegoro University, 2017)
Home Based Enterprise (HBE) develepment of cassava processing in Salatiga City, especially in RW 2 and RW 11, Ledok Sub-district must be optimized and developed in a sustainable manner considering the contribution on social aspect, economic aspect, and region development. This study aims to determine the level of sustainability in HBE of cassava processing in internal factors based on assets analysis in sustainable livelihood approach which includes natural asset, physical asset, human asset, financial capital and social capital and also from external factors such as the availability of policy support in the development of cassava processing HBE at local government level. The method used is mix method with Rapid Appraisal Analysisi called RAP-HBE and kualitative descriptive. The study findings were obtained four (4) of the five (5) of assets in the category of sustainable enough to the value sustainability index consecutive financial capital (72.04), natural capital (67.97), human capital (66.86) and physical capital (53.97). While the social capital obtain the value of sustainability index low of 44.05 and in the category of less sustainable. While external factors such as support by government of Salatiga on the sustainability of HBE in general as well as business training, business assistance, the discussion of business, and others are already there, but HBE processing of cassava that is not a target of the implementation of the policy, so far the sustainability of HBE has not received direct support from the Government of Salatiga.